PENEGAKAN KODE ETIK OLEH BIDANG PROFESI DAN PENGAMANAN POLISI RESOR KOTA PEKANBARU TERHADAP ANGGOTA POLISI YANG MELAKUKAN PELANGGARAN DAN PENYIMPANGAN DALAM PELAKSANAAN TUGAS POLISI ATAS ADUAN MASYARAKAT - Johan Johan; Erdianto Effendi; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The National Police of the Republic of Indonesia in addition to havingbasic duties, functions and authorities, as a good and strong organization hasinternal rules of conduct as operational norms. The rules of order are in the formof rules of discipline and codes of ethics. The rules that police institutions haveare the rules about discipline as honor that are closely related to the credibility,commitment and discipline of members of the Indonesian National Police. In thiscase the credibility and commitment of members of the Indonesian republic'spolice force are as state officials who are given the duty and authority asprotectors, protectors and public servants, law enforcers and carers.The problem that the author makes the basis of this research is how toenforce the code of ethics by the profession and safeguard the town of pekanbarupolice officers against police officers who commit violations and irregularities incarrying out police duties on public complaints, whether barriers to enforcementof codes of ethics and safeguarding the town resort police last week against policeofficers who commit violations and irregularities in carrying out police duties onpublic complaints and how are the strategies and efforts of the professional sectorand security of pekanbaru city resort police to overcome implementationobstacles in enforcing the code of ethics against police officers who commitviolations and irregularities in carrying out police duties on public complaintsThis type of research can be classified into a type of empirical orsociological research, because in this study the author directly conducts researchon the location or place under study in order to provide a complete and clearpicture of the problem under study. This research was conducted at thePekanbaru City police station office, the data sources used were: primary dataand secondary data, data collection techniques in this study by observation,interviews and literature review.The results of the research are first, the process of handling the police whoviolates the police professional code of ethics in committing violations of criminalacts is basically carried out in accordance with the provisions of the CriminalProcedure Code (KUHAP), by remembering, paying attention and adhering to theprovisions governing specifically for suspected members of the IndonesianJOM Fakultas Hukum Volume VI Nomor II Juli-Desember 2019 2National Police as described above, secondly In carrying out enforcement ofviolations of the National Police Professional Code of Ethics there are obstaclesand obstacles as follows: (1) Frequent changes in internal legal rules within theNational Police, (2) Less number of personnel (3) lack of facilities or facilitiesthat are inadequate, the last a) Guidance with verbal speech, a) Guidance withverbal interview, (b) Session of disciplinary cases of violations, (c) The process isas follows: receipt of reports / complaints, examination by provos, disciplinaryexamination, prosecution, vonnis implementation, recording in personnel data.Keywords: Codeof Ethics, Police, Enforcement